GEOINFORMATION TECHNOLOGIES IN THE TRAINING OF FUTURE MINING ENGINEERS - Vladimir S. Morkun; Serhiy O. Semerikov; Svitlana M. Hryshchenko (Інформаційні технології і засоби навчання)
Modern world cannot live without digital technologies. Digital technologies have reached an unprecedented flourishing. The constant growth of information has led to the emergence of many opportunities for digital transactions in various professions, one of which is the mining engineer. The process of reforming this profession requires more efficient use of digital technologies in the environment, ensuring information management through the introduction of innovations, creation of databases, programs, the implementation of which will improve the quality of management of innovation processes. One of the promising directions of solving this problem is the use of geoinformation technologies. Ukraine's interest in increasing the number of engineers is manifested, in particular, in measures to encourage applicants to enter higher education institutions for engineering specialties by providing additional benefits.  In the professional activities of mining engineers, information technologies make it possible not only to consider the location of production units of a mining company, mineral warehouses and rock dumps of a mining company at any required level of detail, but also to help meet the basic environmental requirements in the field of mining.  The program of experimental research to test the effectiveness of methods of using Geoinformation technologies in the formation of environmental competence was implemented in three stages: analytical and stating, design and search and forming and generalizing. The discrepancies identified at the analytical and stating stage of the pedagogical experiment required the development of a new competence system with separate components of environmental competence. Multifunctional geographic information systems were used in the laboratory classes of the control groups, and multifunctional GIS, mining and environmental GIS and the software component of the methodological complex "EcoKryvbas" were used in the experimental ones. Upon completion of the experimental training, it was found that 49.33% of the students in the control groups reached an average level of environmental competence, 20% reached a sufficient level, while in the experimental groups 37.33% of the students reached a sufficient level and 36% reached an average level. In the continuation of scientific research of this problem, it is advisable to develop a methodological system of teaching Geoinformation technologies for students of specialty 122 "Computer Science".